2000
DOI: 10.1021/ol006580m
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Synthesis of 2-Amino-4H-benzothiazines

Abstract: The benzothiazine nucleus is a relatively unexplored class of compounds, from the standpoint of both synthetic chemistry and biological activity. We have developed a rapid, high-yielding synthesis of benzothiazines in which a precursor aryl thiourea is prepared on solid phase. Addition of trifluoroacetic acid catalyzes a conjugate addition reaction to form the desired heterocycle and releases it from the resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…Since the signal of the NH group in the 1 H NMR spectrum of the solution of the compound obtained from thiourea 3b appears at 7.25-7.33 ppm (see Table 2 and our previous work [24]), which is in accord with the chemical shifts of the corresponding protons of the compounds 4a-i, and 5a,c,d (Table 2) and with the chemical shifts of the corresponding protons described in the literature for this type of heterocyclic compounds [20][21][22][23], it is quite likely that the heterocyclic product, which is formed upon the rearrangement of 3b, is present in solution as 2-amino-4H-3,1-benzothiazine 5b, though that this product exists in the crystal as tautomer 6b.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Since the signal of the NH group in the 1 H NMR spectrum of the solution of the compound obtained from thiourea 3b appears at 7.25-7.33 ppm (see Table 2 and our previous work [24]), which is in accord with the chemical shifts of the corresponding protons of the compounds 4a-i, and 5a,c,d (Table 2) and with the chemical shifts of the corresponding protons described in the literature for this type of heterocyclic compounds [20][21][22][23], it is quite likely that the heterocyclic product, which is formed upon the rearrangement of 3b, is present in solution as 2-amino-4H-3,1-benzothiazine 5b, though that this product exists in the crystal as tautomer 6b.…”
supporting
confidence: 84%
“…* 2 The designations R for 4a-i are the same as for 2a-i. An additional finding confirming the correct identification of the transformation products of cyclopropanes 2a-i and 3a-d was the total correlation of the spectral characteristics of heterocycles 4a-i and 5a-c ( Table 2) with the corresponding characteristics of numerous analogs (see, for example, the work of various authors [20][21][22][23]). _______ * The 1 H NMR spectra were taken in CDCl 3 for 2a-e,g,h, and 3a-c and in DMSO-d 6 for 2f, i, 4a-i, and 5a-d. * 2 Here and subsequently, the atoms in the aryl substituent R are indicated with a prime sign.…”
mentioning
confidence: 66%
“…To confirm the structure of the product, 1 H NMR spectra recorded in different deuterated solvents were studied. The compound produces a signal at  6.7 in CDCl 3 , which is in accord with the chemical shift of the exocyclic N-H group [20,21] readily undergoes tautomeric transformation from 4a into 3a. It can be confirmed that solvent conditions play an important role in affecting the tautomeric equilibrium.…”
Section: Resultsmentioning
confidence: 54%
“…A number of methods for the synthesis of 3,1-benzothiazines are currently known. All of them are based on the reactions of arylthioureas containing a halomethyl [1][2][3], hydroxymethyl [1,[4][5][6][7], alkoxy-or acyloxymethyl [1], or immobilized alkenyl fragment [8] in the ortho position of the aromatic ring.…”
mentioning
confidence: 99%